Pengaruh Bauran Pemasaran dan Kesadaran Merek Terhadap Keputusan Pembelian di Usaha Baked Foursion - Eka Putri, Jesica Septiani Eka Putri Septiani; Aditya, Michael Khrisna; Prabandari, Wijayanti Dewi (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan Digital, 2026)
This study aims to analyze the influence of marketing mix and brand awareness on purchase decisions at Baked Foursion. This research employed a quantitative approach using a survey method. Data collection was conducted through questionnaires distributed to 100 Baked Foursion consumers selected using a purposive sampling technique. Data were analyzed using IBM SPSS Statistics through validity testing, reliability testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination analysis. The results showed that the marketing mix had a positive and significant effect on purchase decisions with a significance value of 0.000. Brand awareness also had a positive and significant effect on purchase decisions with a significance value of 0.000 and was found to be a more dominant variable compared to the marketing mix. Simultaneously, marketing mix and brand awareness had a significant effect on purchase decisions, with an R Square value of 0.772. This study indicates that effective marketing strategies and strengthening brand awareness are important factors in improving consumer purchase decisions at Baked Foursion.   Keywords: marketing mix, brand awareness, purchase decision